UTILIZATION OF CHITOSAN FROM SHRIMP SHELLS WASTE FOR REDUCTION IRON (Fe) METAL CONTENT IN MARTAPURA RIVER - Hesti Wijayanti; Hijratul Wahdi; Winardi Nooryanto (Konversi, 2020)
The Martapura River in South Kalimantan contains quite high levels of metals, namely Fe metal which allows the presence of excessive metal elements. According to KEPMENKES, clean water standards contain Fe of 0.3 mg/L. Based on testing, the Fe content contained in the Martapura River water was 2.8 mg/L. One effort to reduce the content of these metals is using adsorbents made from shrimp shells. This shrimp shell waste contains chitin, so if further treatment is given, it is expected to be used as an adsorbent to reduce Fe levels in the Martapura River.The study was conducted using shrimp shells with sizes of 1000 microns, 710 microns and 500 microns. This shrimp shell is deproteinized, the shrimp shell is added with a 3.5% NaOH solution (w/v). Then the demineralization process is carried out, where the dry residue obtained from the previous process is added with 1N HCl solution in a ratio of 1:15 (w/v). From this process chitin is produced, then chitin is deacetylized with 50% NaOH (w/v). Then the samples were tested with a DR-2500 spectrophotometer after being passed to a continuous adsorption device. From the results of the study, it was found that chitosan is very effective in reducing Fe metal content in the Martapura River, the quality of clean water produced reaches the clean water quality standards set. The results of the study at 500 microns size obtained the smallest Fe metal content of 0.05 mg/L.